A study on the operation and management of sanitary landfill in Kelantan / Che Adawiah Che Hashim - Che Hashim, Che Adawiah (Faculty of Architecture, Planning and Surveying, 2010)
Sanitary landfills in the industrialized countries are supposed to be built with optimized and adopted top and bottom liner systems, but most landfills are simply large but shallow holes in the ground filled with waste. Many of these landfills are located based on convenience rather than hydrogeology studies and consequently have been situated in environmentally sensitive marshlands, abandoned mines, and river beds. Consequently locations of landfills have to be selected according to set hydro geological criteria with emphasis on monsooning conditions. Decisions about the landfill management have been taken without any kind of feasibility study and without assessment of the possible consequences of the landfill impacts, so far. Landfills have been designed without any environmental protection measures. National regulations in this region often set standards for environmental protection from landfills that are far above what can reasonably be afforded. It is clear that changing from dumping to advanced standards of sanitary landfilling. The key to such change must be, with the benefit of today's scientific knowledge, the introduction of incremental improvements in the design standards of disposal. Landfill also can be improved with the proper and standard management. Besides that, the government should be prepare the budget to make sure all the landfill site can operate in standard method or follow the requirement from the Department of Environment. At least, the method will be implement in site can control the pollution on environment and than it can be save our earth for the future.